Innovative Aspects of Teaching Foreign Students to Read in English during Distance Learning - Semian, Nataliia V. (2021)
This study examines the issues of teaching foreign students to read in English in the period of distance learning. The relevance of the problem under study is driven by the need for implementation of non-standard systems of teaching students the reading techniques in response to the quarantine isolation, due to the inability to undergo training according to the standard scheme. The purpose of the paper is to investigate and determine the main directions to consider the problem at hand, with an indication of its specific innovative solutions. A combination of analytical and logical research methods with a detailed analysis of available studies in the chosen field was chosen as the leading approach to the investigation of this question. The main results of this paper are: a statement of the availability of unlimited opportunities in this field, with the development of the Internet-based teaching technologies, and the recognition of the fact that the level of technical equipment of Ukrainian universities corresponds to that necessary for conducting successful classes with foreign students online in order to teach them to read in English. Prospects for further research in this area are determined by the urgent need for the development of distance learning in general and to teach foreign students to read in English, in particular, using innovative solutions that increase the overall efficiency of the teaching process.